2011
DOI: 10.1002/hbm.21389
|View full text |Cite
|
Sign up to set email alerts
|

Preferential networks of the mediodorsal nucleus and centromedian–parafascicular complex of the thalamus—A DTI tractography study

Abstract: Distinct thalamic nuclei, like the mediodorsal (MD) nucleus and the centromedian/parafascicular complex (CM/Pf), are embedded in different basal ganglia-thalamocortical loops, which were shown to integrate cognitive and emotional aspects of human behavior. Despite well described connections on a microscopic scale, derived from tracing studies in animals, little is known about the intrinsic anatomical connections of these nuclei in humans. This lack of knowledge limits not only interpretation of functional imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 76 publications
(130 reference statements)
5
68
0
Order By: Relevance
“…3 and 4) analysis and weakly at the inter-individual (Fig. 8) analysis, follows a well-described anatomical route of a preferential anatomical connectivity (Eckert et al, 2012) and salience related activations (Metzger et al, 2010). This overlap, which would indeed speak in favor of a common framework to explain dynamics of connectivity as representations varying psychological states, needs however to be regarded with caution due to the weak significance and potential bias (specificity) by the length of the sliding window used for analysis.…”
Section: Discussionmentioning
confidence: 54%
“…3 and 4) analysis and weakly at the inter-individual (Fig. 8) analysis, follows a well-described anatomical route of a preferential anatomical connectivity (Eckert et al, 2012) and salience related activations (Metzger et al, 2010). This overlap, which would indeed speak in favor of a common framework to explain dynamics of connectivity as representations varying psychological states, needs however to be regarded with caution due to the weak significance and potential bias (specificity) by the length of the sliding window used for analysis.…”
Section: Discussionmentioning
confidence: 54%
“…Other targets include the globus pallidus, the anterior limb of the internal capsule, the nucleus accumbens, and the subthalamic nucleus. 19 The role of the CM-Pf in motor and executive functions such as attention and motor control 2022 and its connections with many subcortical regions 22,23 may contribute to the efficacy of CM-Pf DBS for TS. The literature suggests good tic control with CM-Pf DBS.…”
Section: Discussionmentioning
confidence: 99%
“…The striatum receives most of the CM-Pf efferents. Although Eckert et al (10) recently confirmed the extended connectivity between CM-Pf and subcortical structures in a tractography study of normal human subjects, CM-Pf connections have been mainly investigated in studies in rodents and primates, which found that CM (or its rodent equivalent, the lateral Pf nucleus) and Pf have complementary functions.…”
Section: The Role Of the Cm-pf In Tourette’s Syndromementioning
confidence: 99%